2014
DOI: 10.4014/jmb.1308.08060
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Antibiotic Produced by Bacillus subtilis JW-1 that Suppresses Ralstonia solanacearum

Abstract: Bacillus subtilis JW-1 was isolated from rhizosphere soil as a potential biocontrol agent of bacterial wilt caused by Ralstonia solanacearum. Seed treatment followed by a soil drench application with this strain resulted in >80% reduction in bacterial wilt disease compared with that in the untreated control under greenhouse conditions. The antibacterial compound produced by strain JW-1 was purified by bioactivity-guided fractionation. Based on mass spectroscopy and nuclear magnetic resonance spectral data ((1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 16 publications
(18 reference statements)
0
17
1
Order By: Relevance
“…These results are contrariwise those of Kheirandish and Harighi (2015) who found that different strains of P. fluorescens antagonized the growth of R. solanacerum. Also, these results are on the contrary of those of Kwon and Kim (2014) who demonstrated that B. subtilis suppressed the growth of R. solanacerum. In addition, Nath et al (2016) had counteractive results of this investigation where they showed that B. subtilis and P. fluorescens inhibited the growth of R. solanacearum.…”
Section: Inhibition Effects and Micscontrasting
confidence: 94%
“…These results are contrariwise those of Kheirandish and Harighi (2015) who found that different strains of P. fluorescens antagonized the growth of R. solanacerum. Also, these results are on the contrary of those of Kwon and Kim (2014) who demonstrated that B. subtilis suppressed the growth of R. solanacerum. In addition, Nath et al (2016) had counteractive results of this investigation where they showed that B. subtilis and P. fluorescens inhibited the growth of R. solanacearum.…”
Section: Inhibition Effects and Micscontrasting
confidence: 94%
“…Many studies have shown that the use of Bacillus strains as biological control agents is as a promising and safe strategy for effective tomato bacterial wilt management. Kwon and Kim reported that B. subtilis JW-1 could lead to a >80% reduction in bacterial wilt disease and can be used as a potential biocontrol agent of tomato bacterial wilt [42]. Xiong et al isolated the B. amyloliquefaciens JK6 strain and found that it could effectively suppress tomato bacterial wilt with biocontrol efficacies for up to 52.9% under two greenhouse conditions [39].…”
Section: Discussionmentioning
confidence: 99%
“…Bais et al reported that B. subtilis 6051 was able to control Pseudomonas syringae root infection in Arabidopsis because of the secretion of surfactin and the formation of a biofilm on the plant roots [15]. Kwon and Kim demonstrated that B. subtilis JW-1 induced a significant bacterial wilt disease suppression effect in vivo due to the production of cyclic lipopeptides [42]. Xiong et al reported that the secretion of surfactin by the strain JK6 played important roles in the biocontrol of tomato bacterial wilt [39].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that the use of Bacillus strains as biological control agents is as a promising and safe strategy for effective tomato bacterial wilt management. Kwon and Kim reported that B. subtilis JW-1 could lead to a >80% reduction in bacterial wilt disease and can be used as a potential biocontrol agent of tomato bacterial wilt [41]. Xiong et al isolated the B.…”
Section: Velezensismentioning
confidence: 99%
“…Bais et al reported that B. subtilis 6051 was able to control Pseudomonas syringae root infection in Arabidopsis because of the secretion of surfactin and the formation of a biofilm on the plant roots [15]. Kwon and Kim demonstrated that B. subtilis JW-1 induced a significant bacterial wilt disease suppression effect in vivo due to the production of cyclic lipopeptides [41]. Xiong et al reported that the secretion of surfactin by the strain JK6 played important roles in the biocontrol of tomato bacterial wilt [38].…”
Section: Velezensismentioning
confidence: 99%